Speech Wheel: An Intervention in Reducing Speaking Aporia of Freshmen English Major Students - Jacquiline B. Frago; Maria Cristal N. Velez; Claudine A Torrero Torrero (Journal of English Education and Linguistics, 2021)
Speaking aporia is a usual problem for many learners that hinder them to communicate and affects their learning performance. It is defined as a distinct complex of self-perceptions, beliefs, feelings, and behaviors related to the use of second language for communication. This encouraged the researchers to come up with a study of reducing the speaking aporia through Speech Wheel to develop speaking skills, enhance critical thinking, and boost confidence and motivation. Having the Freshmen English Major students of University of Nueva Caceres as the respondents, this study determined the following (1) the causes of speaking aporia; (2) the level of speaking aporia; and (3) the effects of the Speech Wheel as an intervention. Through descriptive quantitative method, the researchers were able to identify the following factors that cause the speaking aporia of the respondents: (1) 25 % of them has the fear of standing in front of large groups; (2) 20 % has concern that others are judging them and; (3) 13 % of them fear that they might appear nervous. Using the same method, the researchers found out that 50% of the respondents have moderate level of speaking aporia. Moreover, descriptive qualitative method was used to identify the effects of Speech Wheel to the students along with stress, motivation, and self-confidence, these include the following: (1) it reduced the stress level of the students in terms of speaking as they enjoyed the activity; (2) their self-confidence and motivation improved especially in speaking in front of the large groups of people; and (3) it stimulated the students in speaking. The researchers concluded that factors that affect students’ ability in speaking were shown through their stress, motivation, and self-confidence. Speech wheel is an effective intervention to reduce the speaking aporia of the students and the researchers recommend that it must be used as an intervention that exposes the students to be more confident and boosts their self- confidence.